Climate change and agricultural resilience in India: Challenges and strategies - Vishwambhar Nath Sharma (National Geographical Journal of India, 2024)
Due to human intervention in nature, climate characteristics, weather patterns, and climate effects have been continuously changing in recent years. There has been an increase in the frequency and intensity of extreme climate events. Climate change has become a significant global challenge today. Extreme events such as excessive heat, drought, floods, and changes in normal weather patterns have impacted agriculture, water supply, infrastructure, education, health and rural livelihood. The crop rotation, soil fertility, and various aspects of the agricultural system have been affected, ultimately influencing agro-production and productivity. These weather changes have led to the emergence of various new pests and diseases that are causing significant damage to crops and livestock. Poor families become more vulnerable to extreme events because they lack alternative sources of income. This paper aims to highlight the impacts of changing patterns of weather conditions due to climate change on agricultural activities and the rural economy and also to explore the challenges and adaptive strategies to make the villagers resilient to these impacts. Internet sources and other electronic media, newspapers, books and journals are consulted for this study.